THE INFLUNCES OF USING PICTURES SERIES IN STUDENTâS WRITING COMPOSITION TO THE EIGHTH GRADE STUDENTS OF SMP PGRI 1 PALEMBANG - Pratiwi, Etty (Jurnal Dosen Universitas PGRI Palembang, 2016)
Abstract: this research investigated the influence of using pictures series in studentâs writing compositionÂ  to the eighth grade students of SMP PGRI 1 Palembang. The objective of this study was to identify whether or not by using pictures series can improve the students â writing composition. This study was conducted in experimental research to 82 students from the eighth grade students of SMP PGRI 1 Palembang of the academic year of 2016-2017. This study could be concluded that pictures series strategy gave a significant improvement for the studentsâ writing composition than the studentsâ writing composition by using conventional strategy to the eighth grade students of SMP PGRI 1 Palembang.Â Key Words:Â  Pictures stories, Writing Composition